Studi Kuantitatif: Numbered Heads Together Terhadap Hasil Belajar Peserta Didik Madrasah Ibtidaiyah - Sidon, Bey Arifin; Haq, Bella Arini; Masruroh, Fitriatul; Khoiri, Agung Fajar (Jurnal Ilmiah Wahana Pendidikan, 2025)
Education is key to improving the quality of human resources who possess academic competence, particularly in terms of religiosity. Learning through Arabic language education is one of the important pillars for improving students' skills in enhancing academic competence. However, there are still weaknesses in the implementation of Arabic language education, making students less interested in learning it. This research aims to obtain empirical evidence regarding the implementation of numbered heads together (NHT) as a learning model that is expected to improve student competence. The research approach used a quantitative with a pre-experimental type through a one-group pre-test-posttest design. The sampling technique was saturated with a total of 21 respondents at MI Miftahul Ulum I Wringinpitu. Data analysis was conducted using SPSS. Based on the research results, empirical findings were obtained that numbered heads together (NHT)-based learning can improve student competence in terms of cognitive, active discussion, responsibility aspects, and social skills of students.